2019
DOI: 10.1074/jbc.tm118.002812
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the endoplasmic reticulum–resident, collagen-specific molecular chaperone Hsp47 in vertebrate cells and human disease

Abstract: Heat shock protein 47 (Hsp47) is an endoplasmic reticulum (ER)-resident molecular chaperone essential for correct folding of procollagen in mammalian cells. In this Review, we discuss the role and function of Hsp47 in vertebrate cells and its role in connective tissue disorders. Hsp47 binds to collagenous (Gly-Xaa-Arg) repeats within triple-helical procollagen in the ER and can prevent its local unfolding or aggregate formation, resulting in accelerating triple-helix formation of procollagen. Hsp47 pH-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 94 publications
3
113
0
Order By: Relevance
“…The role of TNC in promoting pulmonary fibrosis is also supported by attenuation of bleomycin-induced fibrosis in Tnc-deficient mice 52 . In addition, we found SER-PINH1, a chaperone involved in collagen maturation 53 , among the commonly upregulated matrisome proteins. SERPINH1, has been shown to be increased in AT2 cells and myofibroblasts of IPF patients, where it induces overexpression of type I procollagen contributing to the general tissue disorganization 54 .…”
Section: Actb Total Smad3mentioning
confidence: 82%
“…The role of TNC in promoting pulmonary fibrosis is also supported by attenuation of bleomycin-induced fibrosis in Tnc-deficient mice 52 . In addition, we found SER-PINH1, a chaperone involved in collagen maturation 53 , among the commonly upregulated matrisome proteins. SERPINH1, has been shown to be increased in AT2 cells and myofibroblasts of IPF patients, where it induces overexpression of type I procollagen contributing to the general tissue disorganization 54 .…”
Section: Actb Total Smad3mentioning
confidence: 82%
“…PCPE‐1 may also function as a chaperone required for procollagen stability and/or transport. Similar functions have been ascribed to Hsp47, a collagen‐specific chaperone that in addition to stabilization of the collagen triple helix has been shown to mediate interaction of procollagens with transmembrane protein transport and Golgi organization 1 (TANGO1), a protein involved in loading procollagen molecules into special coat protein complex II (COPII) vesicles for transport (Ishikawa et al, ; Maiers et al, ; Raote et al, ; Ito and Nagata, ). Dependence of PCPE‐1 secretion and membrane localization on Asc may reflect such an association between PCPE‐1 and procollagen secretion.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, HSP47 is strongly associated with collagen-related brotic diseases, including liver, heart, kidney and pulmonary brosis. [2] We have reported that HSP47 expression is upregulated and associated with progression of pulmonary brosis and pulmonary brotic disorders using animal models of the same in humans. [3][4][5][6][7] HSP47 has also been reported to be associated with several types of cancers, including cervical, breast, pancreatic, gastric, and colon cancer.…”
Section: Introductionmentioning
confidence: 97%